RANCANG BANGUN ALAT PENDETEKSI TEGANGAN LISTRIK UNTUK TEKNISI INDIHOME DI PT. TELKOM AKSES WITEL MAKASSAR - Andi Muhammad Arif Bijaksana; Ardyansah Ardyansah; Farida Farida; Masfuad Muttaqin NH (Jurusan Teknik Elektro, Fakultas Teknik, Universitas Borneo Tarakan, 2019)
The development of internet network infrastructure in Indonesia is inseparable from the presence of technicians to turn on or distribute internet services to the customer's home. Not infrequently the technicians experience work accidents due to electric shock. The number of work accidents due to electric shock pushed us to design a device that is able to detect electricity early or remotely and easy to use independent technicians so as to minimize work accidents due to electric shock. The objectives of this study are: 1) Designing a voltage detector located around the location of the indihome technician's work. 2) Implement an electric voltage detector on indihome technicians. By using a tool design method designed using applications such as Electronics Workbench (EWB), PCB Express (Printed Circuit Board), Sketchup. And also assembled using tools materials that are easily found in electronic stores. LED (Light Emitting Diode Buzzer serves as an indicator of the presence of electrical hazards around the technician's work location. The results of this study are: 1) This tool is able to detect electrical voltages from a minimum distance of 0 mm to 400 mm. 2) This tool is shaped like a watch so that it is easy to use indihome technicians in working and does not interfere with the work process.